2021
DOI: 10.1177/00131245211026689
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Responsive Teaching in Urban Secondary Schools

Abstract: Demographic data show an increasingly diverse student population in all urban settings. On the other hand, there continues to be a discrepancy about the student population and the teacher force, as the majority of the US teachers are predominately middle class, female, monolingual, and of European ancestry. This discrepancy adds complexity to an already complex profession. To bridge this cultural gap, researchers advocate for a change in the teaching paradigm, in which teachers understand the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The dearth of literature focused on evaluating CRT practices may be due to the inconsistent interpretations of the CRT framework (Cervantes & Clark, 2020). There are numerous CRT-related theories to draw from, including culturally responsive pedagogy (Chang & Viesca, 2022), CRT (Tanase, 2022), and culturally relevant teaching (Byrd, 2016). A plethora of studies are being published simultaneously to unpack these theories and how they can best be represented in the classroom, which can cause misconstruals across theories.…”
Section: Discussionmentioning
confidence: 99%
“…The dearth of literature focused on evaluating CRT practices may be due to the inconsistent interpretations of the CRT framework (Cervantes & Clark, 2020). There are numerous CRT-related theories to draw from, including culturally responsive pedagogy (Chang & Viesca, 2022), CRT (Tanase, 2022), and culturally relevant teaching (Byrd, 2016). A plethora of studies are being published simultaneously to unpack these theories and how they can best be represented in the classroom, which can cause misconstruals across theories.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be related to the characteristics of the interpersonal relationships that leaders build with novice teachers. For example, novice teachers who are ethnoracially matched to their principal could experience increased voice, less discrimination, and more support to pursue culturally responsive teaching practices (Grissom et al, 2015; Tanase, 2022). Relatedly, Brezicha and Fuller (2019) found that teachers working with the same race/ethnicity principal reported higher levels of trust in their principal.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Tanase (2022) explained that culturally responsive teachers used community assets to teach their students different concepts in mathematics and science, making their students' real-life experiences part of the official curriculum. Classrooms become communities of learners where students work together to learn the content and they develop a critical consciousness about issues and events that occur in their own communities.…”
mentioning
confidence: 99%
“…In other classes, students used gummy bears and marshmallows to build water molecules or used pizza or cookies to learn about fractions. Tanase (2022) further explained how science teachers used examples of water to make the content relevant, such as discussing how the rain affected the environment, or relating water properties to beverages (i.e. lemonade, Kool-Aid).…”
mentioning
confidence: 99%
See 1 more Smart Citation